High prevalence of spotted fever group rickettsiae in ticks collected from yaks (Bos grunniens) in Shiqu county, eastern Tibetan Plateau, China - Lin, Baoshan; Ta, Yin; Hao, Lili (Frontiers in Microbiology, 2022)
Tick-borne diseases have become a global health concern in recent decades. Spotted fever group (SFG) rickettsiae have been recognized as important pathogens of human tick-borne diseases worldwide. In this study, Dermacentor everestianus (n= 646) and Haemaphysalis qinghaiensis (n= 172) ticks were collected from yaks (Bos grunniens) in Shiqu county, eastern Tibetan Plateau, China. SFG rickettsiae were identified and characterized in these ticks. A total of 49.9% (408/818) ticks were infected by Rickettsia spp. with infection rates of 58.1% (100/172) and 46.7% (308/646) detected in H. qinghaiensis and D. everestianus ticks, respectively. Furthermore, 95% of Rickettsia spp. were Rickettsia raoultii-like bacteria, and 5% were related to Candidatus Rickettsia longicornii. However, no SFG rickettsiae infections have previously been reported in Shiqu county for these tick species. Our results indicated that H. qinghaiensis and D. everestianus ticks from Shiqu county became highly infected with a R. raoultii-like bacteria during their feeding process. The prevalence of R. raoultii-like bacteria in livestock and wildlife hosts should be further investigated in the future.